F3R-skew cyclic codes. (2016) - Sharma, Amit; Bhaintwal, Maheshanand
In this paper, a new class of skew-cyclic codes, termed as F3 R-skew cyclic codes, is defined, where R denotes the ring F3 + uF3, u 2 = u. These codes are of length α + β and are submodules of the R-module F3 α R β . We study some structural properties of skew cyclic codes over R and F3 R-skew cyclic codes. The generator polynomials of these codes are studied. Some examples are given to illustrate the results. An optimal ternary code is obtained as the Gray image of an F3 R-skew cyclic code.